2007
DOI: 10.1016/j.jeconom.2007.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Time and causality: A Monte Carlo assessment of the timing-of-events approach

Abstract: We present new Monte Carlo evidence regarding the feasibility of separating causality from selection within non-experimental duration data, by means of the non-parametric maximum likelihood estimator (NPMLE). Key findings are: (i) the NPMLE is extremely reliable, and it accurately separates the causal effects of treatment and duration dependence from sorting effects, almost regardless of the true unobserved heterogeneity distribution; (ii) the NPMLE is normally distributed, and standard errors can be computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
199
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(205 citation statements)
references
References 35 publications
(47 reference statements)
2
199
0
4
Order By: Relevance
“…We maximize this log-likelihood according to the procedure described in Gaure et al (2007). In particular, we increase the number of points of support until the likelihood function does not show any improvement and subsequently select the model that minimizes the Akaike Information Criterion (AIC) to reduce the risk of bias induced by an over-parameterized model.…”
Section: O V E R E D U C a T I O N A T T H E S T A R T O F T H E C mentioning
confidence: 99%
See 2 more Smart Citations
“…We maximize this log-likelihood according to the procedure described in Gaure et al (2007). In particular, we increase the number of points of support until the likelihood function does not show any improvement and subsequently select the model that minimizes the Akaike Information Criterion (AIC) to reduce the risk of bias induced by an over-parameterized model.…”
Section: O V E R E D U C a T I O N A T T H E S T A R T O F T H E C mentioning
confidence: 99%
“…Even if the time grouping of the data is not problematic, Monte Carlo analysis of Gaure et al (2007) has shown that that it is important to take, as we do (see Appendix B), this time grouping explicitly into account. However, if one follows this advice the aforementioned Monte Carlo analysis has shown that Abbring and van den Berg (2003)'s method is extremely reliable.…”
Section: Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaure et al (2007) provide extensive Monte Carlo evidence that the parameters of the underlying continuous time model can be recovered using discrete data, so long as the likelihood function reflects the discrete nature of the available data. This allows exit rates to vary flexibly over the duration of the spell.…”
Section: Identificationmentioning
confidence: 99%
“…16 We were able to estimate the model with up to three points of support. Following (Gaure et al, 2007), it is common to use the Akaike Information Criterion (AIC) to help inform the choice of M. Of the three specifications, M = 3 minimised the AIC and was therefore adopted as the preferred specification. 17 Calculated as exp(0.092)-1=0.0957.…”
Section: Identificationmentioning
confidence: 99%